Pengaruh Investasi Dan Inflasi Terhadap Jumlah Penduduk Miskin di Kabupaten Jember Tahun 2000-2015 - Abdul Latif Hamzah; Anifatul Hanim; Herman Cahyo (UPT Penerbitan Universitas Jember, 2019)
Conditions in Jember Regency from year to year economic growth is quite high, but the poverty level is very high as well. This study aims to determine the effect of investment and inflation on the number of poor people in the district of Jember in 2000- 2015. The method used in this research is multiple linear regression. The data used are secondary data formed in time series, the data used include investment, inflation in Jember district for 16 years in the year 2000-2015. Based on the results of the research, it can be seen that investment variables do not significantly affect the number of poor people in Jember, while Inflation has a significant effect on the number of poor people in Jember. Keywords: total investment, inflation, and poor people.